Evaluation of CPK (Creatinine Phosphokinase) in Hypertensive Patients used either Statin and/or Ezetimibe - Jawad F.H. Al-Musawi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: The effectiveness of cholesterol in the improvement of cardiovascular disorder used to be proven in the 2d half of of the twentieth century. Cholesterol researcher Daniel Steinberg writes that whilst the 1984 Primary Coronary Prevention Study confirmed that reducing ldl cholesterol substantially reduces the chance of coronary heart assault and angina, clinicians, consisting of cardiologists, mostly disagree. Not convinced. In the 1990s, after a public marketing campaign in the United States to instruct human beings about ldl cholesterol ranges and the distinction between HDL and LDL cholesterol, countless pharmaceutical businesses started out producing their personal statins. Ezetimibe is a drug used to deal with excessive blood ldl cholesterol and some different lipid disorders. It is frequently used with dietary adjustments and statins. It's now not as famous as statins.Aim: To reflect the serous side effect of combination of both Ezetimibe and Statin in elevation of CPK. Patients and Methods: In this study, patients (50-75) will be divided into three organizations:1-The first group which were treated only by Statin which were (145) patients2-Second group which were treated by Ezetimibe were (140) Patients.3-The third group who treated by both Statin and Ezetimibe were (142) Patients.4- The total number were (427).All the patients which were investigated regularly by each of their visit and, lab measurement of serum PCK in each visit. And all the patients were followed and also each patient received Statin, Ezetimibe or both of these drugs for 3 months and during these three months they followed and investigated completely. Results: We found 145 patients (33.94%) responded to simvastatin 40mg/day when compared to those patients who treated by Ezetimibe 10mg/day which were 140(32.75%), While 142(33.25%) patients had good response when treated by combination of both Simvastatin and Ezetimibe Simvastatin10mg/ day, and statin 10mg/day. And 67(15.70%), complained from Rhabdomyolysis, in those patients treated by Ezetimibe 10mg/day. While 105(24.60%), were complained from Rhabdomyolysis, in those patients treated by a combination of both Ezetimibe 10mg/ day, and statin 10mg/day. We conclude from this study that; although there is significant effect of Statin and Ezetimibe in lowering Serum Lipids in general, but there is a serious increase of CPK which lead to Rhabdomyolysis, especially when moderately high doses of combination were used